Cochrane Review Summaries—July 2020. Issue 1 (July 2020) - Jahanfar, Shayesteh; Hill, Matthew; Kariyawasam, Diluma; Kumar, Nimisha; Haas, David M.
Abstract : This feature highlights recently published Cochrane Reviews of interest to the readers of Obstetrics & Gynecology . The brief summaries are published below, and the complete references, along with a hyperlink, are listed in Box 1.